Comparison between 80-microns versus 100-microns flap femtosecond LASIK for correction of myopia and myopic astigmatism - Sudarshan Khokhar; Deeksha Rani; Hemant Jhajharia; Saumya Kumar; Aishwarya Rathod; Sarika Rajput (Indian Journal of Ophthalmology, 2024)
Purpose: This study aimed to compare the safety, efficacy, and visual outcomes of 80-microns LASIK versus 100-microns LASIK in managing myopia and myopic astigmatism. The study was conducted at a tertiary care hospital in North India. Methods: This was a prospective contralateral eye study that included patients with myopia and myopic astigmatism seeking refractive correction. The eligibility criteria included normal corneal topography, an epithelial thickness less than 60 microns, a calculated percentage tissue ablation (with 100-microns flap) less than 40%, a calculated residual stromal bed thickness (with 100-microns flap) more than 300 microns, and willingness to participate and follow up. Patients with glaucoma, cataracts, other visually disabling ocular pathologies, and a history of past ocular surgery were excluded. All patients underwent LASIK with 80-microns LASIK in one eye and 100-microns LASIK in the other eye. The patients were followed up for 6 months, and the results were analyzed. Results: The study included 216 eyes of 108 patients. The mean preoperative spherical equivalent in the 80-microns group and the 100-microns group was -3.53 ± 1.81 and -3.69 ± 1.32 diopters, respectively (P = 0.78). The mean 6 months decimal postoperative UCVA was 0.98 ± 0.13 in the 80-microns group and 0.97 ± 0.14 in the 100-microns group (P = 0.99). The postoperative change in the higher-order aberration profile was comparable in both groups (P = 0.78). The percentage tissue ablation was significantly lower in the 80-microns group (P = 0.002). The incidence of flap micro striae and OBL was higher in the 80-microns group, while neither of these had any visual implications. Conclusion: The study concluded that 80-microns LASIK is an efficacious and safe alternative to 100-micron LASIK, especially useful in patients with higher myopia.